2008
DOI: 10.1016/j.ejcts.2008.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the time until atrial fibrillation recurrence after concomitant left atrial ablation

Abstract: Preoperative atrial fibrillation duration and left atrial diameter predict the time until atrial fibrillation recurrence after concomitant left atrial ablation, whereas age, type of primary cardiac surgery, ablation technology and antiarrhythmic therapy do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Previous investigators have identified that duration of preoperative AF was a significant predictor of late recurrence of AF . We also found that duration of AF >24 months is an independent predictor of recurrence of AF at 24 and 60 months.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous investigators have identified that duration of preoperative AF was a significant predictor of late recurrence of AF . We also found that duration of AF >24 months is an independent predictor of recurrence of AF at 24 and 60 months.…”
Section: Discussionsupporting
confidence: 77%
“…Though persistent AF and long‐standing persistent AF are more difficult to treat, in our study the type of AF was not a predictor of recurrence of AF. Many studies also demonstrated that the type of AF did not predict AF recurrence …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the duration of preoperative AF is associated with postoperative AF recurrence [30,31]. In our study, the duration of AF was not associated with SR maintenance.…”
Section: Discussionsupporting
confidence: 53%
“…Patients with persistent AF of long duration do not respond as well to medical therapy, or surgical 16 , or catheter ablation. 17 The results of the current study suggest that patients with a longer duration of continuous AF tend to have a higher AF frequency, consistent with more extensive electrical remodeling.…”
Section: Discussionmentioning
confidence: 99%